Attack on Lignified Grass Cell Walls by a Facultatively Anaerobic Bacterium - Akin, Danny E. (1980)
A filamentous, facultatively anaerobic microorganism that attacked lignified tissue in forage grasses was isolated from rumen fluid with a Bermuda grass-containing anaerobic medium in roll tubes. The microbe, designated 7-1, demonstrated various colony and cellular morphologies under different growth conditions. Scanning electron microscopy revealed that 7-1 attacked lignified cell walls in aerobic and anaerobic culture. 7-1 predominately degraded tissues reacting positively for lignin with the chlorine-sulfite stain (i.e., sclerenchyma in leaf blades and parenchyma in stems) rather than the more resistant acid phloroglucinol-positive tissues (i.e., lignified vascular tissue and sclerenchyma ring in stems), although the latter tissues were occasionally attacked. Turbidimetric tests showed that 7-1 in anaerobic culture grew optimally at 39°C at a pH of 7.4 to 8.0. Tests for growth on plant cell wall carbohydrates showed that 7-1 grew on xylan and pectin slowly in aerobic cultures but not with pectin and only slightly with xylan in anaerobic culture. 7-1 was noncellulolytic as shown by filter paper tests. The microbe used the phenolic acids sinapic, ferulic, and p-coumaric acids as substrates for growth; the more highly methoxylated acids were used more effectively.